Visible-ness : the nature of communication between children and health professionals in a specialist children's hospital in the Republic of Ireland: An ethnographic inquiry - Lambert, Veronica Ann (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2009)
Background: Although there is evidence of an emerging body of knowledge exploring children’s views of their information and communication needs, little is known empirically about the communication process between children and members of the healthcare team in inpatient hospital settings. Aim: The aim of this thesis was to explore and describe the nature of communication for children admitted to a specialist children’s hospital setting.
Keywords: Nursing, Ph.D.; Ph.D. Trinity College Dublin